An In-Vitro Comparison and Analysis of Apical Microleakage of Thermafil, System B and Cold Lateral Compaction Obturation Techniques by using Linear Dye Penetration Measurement Method - Jawaed, Noor-ul-Ain; Abidi, Syed Yawar Ali; Niazi, Muhammad Imran Khan; Parvez, Khurram; ., Farah Naz; Ahmed, Shahbaz (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To evaluate and compare the apical microleakage of Thermafil and System B in comparison with cold lateral compaction (CLC) endodontic obturation technique using dye penetration measurement. METHODOLOGY: This in vitro experimental study was conducted from January to June 2014 at the Department of Operative Dentistry. Total 244 extracted human maxillary and mandibular single rooted teeth with intact roots were selected and divided into 3 groups according to obturation method: Group A, carrier based thermo-mechanical compaction (Thermafil); Group B, warm vertical compaction (System B); and Group C, cold lateral compaction (CLC). Protaper universal rotary system (X-Smart) up to file size F3 used to prepare the root canals. 5.25% Sodium hypochlorite (NaOCl) and 17% Ethylenediamine tetra-acetic acid (EDTA) used to irrigate the canals. Samples were engrossed in 2% methylene blue and stored at 37 Cº for 7 days. The root of each tooth was sectioned, and linear dye leakage (LDL) was measured by stereomicroscope. RESULTS: SPSS version 16 was utilized for statistical analysis. To compare the means, Bonferroni test-one-way analysis of variance was performed. For different groups means with standard deviation (SD) of dye penetration were noted as follows: Group A 2.02mm (SD ±0.86), Group B 2.17mm (SD±0.90) and Group C 2.67mm (SD±1.17). The difference between group A and B was statistically insignificant (p=0.586) however in comparison to group C it was significant (p= 0.000). Grade 5 dye penetration was noted in very few cases (12.8%) in group C. CONCLUSION: Leakage found in all the specimens. However, roots obturated with cold lateral condensation leaked the most while Thermafil exhibited least leakage.